Hardware efficient approximate adder design - Balasubramanian, Padmanabhan (2020)
This paper presents a new approximate adder architecture which when implemented on an FPGA consumes fewer logic resources compared to accurate adders of similar size and can achieve higher or comparable operating frequencies. For 32-bit addition, our approximate adder achieves a 25% reduction in the number of LUTs utilized compared to the accurate adder with no compromise on the speed performance. For 64-bit addition, our approximate adder achieves a 24% improvement in the maximum operating frequency, and a 25% reduction in the number of LUTs utilized compared to the accurate adder (post place and route on a Virtex-7 FPGA device). We also make comparisons with the FPGA-based implementations of some well-known gate-level approximate adders, and further provide insights into the error characteristics showing that the proposed approximate adder has a reduced error range.